Underpricing and Index Excess Returns - Peter Nippel; Christian Pierdzioch; Andrea Schertler (Kiel Institute for World Economics (IfW), 2005)
We study the link between underpricing of initial public offerings (IPOs) and index excess returns in secondary markets. We use a theoretical model to argue that underpricing of IPOs raises investors' attention and, thereby, triggers investments in secondary markets. Our theoretical model implies that such investments should give rise to positive index excess returns in secondary markets. The results of our empirical tests, based on a dataset of stocks from the Neuer Markt and the Nouveau Marché, are in line with the implication of our theoretical model.
Keywords: N24; G14; 330; underpricing; index excess returns; IT firms; Börsenkurs; Wertpapieremission; Kapitalertrag; Aktienindex; Neuer Markt; Schätzung; Theorie; Deutschland; Frankreich; Sekundärmarkt